Discovery of potent, highly selective covalent irreversible BTK inhibitors from a fragment hit. Issue 17 (15th September 2018) - Qiu, Hui; Liu-Bujalski, Lesley; Caldwell, Richard D; Follis, Ariele Viacava; Gardberg, Anna; Goutopoulos, Andreas; Grenningloh, Roland; Head, Jared; Johnson, Theresa; Jones, Reinaldo; Mochalkin, Igor; Morandi, Federica; et al.
Graphical abstract: Highlights: A novel series of potent covalent irreversible BTK inhibitors was discovered from a fragment hit. The optimization of the linker part was accomplished with the aid of MOE. The top molecule showed comparable cellular potency to ibrutinib and higher kinome selectivity. Abstract: Bruton's Tyrosine Kinase (BTK) is a member of the TEC kinase family that is expressed in cells of hematopoietic lineage (e.g., in B cells, macrophages, monocytes, and mast cells). Small molecule covalent irreversible BTK inhibitor targeting Cys481 within the ATP-binding pocket, for example ibrutinib, has been applied in the treatment of B-cell malignancies. Starting from a fragment hit, we discovered a novel series of potent covalent irreversible BTK inhibitors that occupy selectivity pocket of the active site of the BTK kinase domain. Guided by X-ray structures and a fragment-based drug design (FBDD) approach, we generated molecules showing comparable cellular potency to ibrutinib and higher kinome selectivity against undesirable off-targets like EGFR.